The Influence of the Work Environment on Employee Work Discipline at the Central Statistics Agency Office, Gowa Regency - Fadhilah Rezkiyanti; Risma Niswaty; Isgunandar Isgunandar (International Journal of Administration and Education (IJAE), 2025)
Human resources are essential to the success of an organization and play a vital role in any agency or institution. "Human resources" is a term used to refer to the workforce or people within an organization. Every organization or institution certainly requires quality human resources and includes aspects such as having expertise, skills, knowledge, and high discipline, which are important foundations in maintaining smooth operations and the success of an organization or institution. This study discusses the influence of the work environment on employee work discipline at the Gowa Regency Central Statistics Agency Office. This study is a quantitative study to identify cause and effect. The sample in this study was 32 people with the probability sampling technique with the simple random sampling method. Data collection techniques were carried out through observation, questionnaires, interviews, and documentation. Data analysis techniques used were descriptive data analysis and inferential statistical analysis. The results of the study indicate that the work environment is in the "Very Good" category with 6 indicators in it: smoothness, security, safety, cleanliness, comfort, and adequate facilities. Meanwhile, work discipline is categorized as "Very Good," with five indicators: attendance rate, work procedures, obedience to superiors, work awareness, and responsibility. Based on the results of a simple linear regression analysis, it was concluded that there is a positive and significant influence between the work environment and employee work discipline at the Gowa Regency Central Statistics Agency Office.